Using blogs to encourage ESL students to write constructively in English - Nadzrah Abu Bakar,; Kemboja Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2009)
This paper reports on a study incorporating blog projects as part of an integrated English project assignment. Students did the project outside classroom hours to practice their language skills in an authentic environment, using blogs to communicate with each other. This study seeks to assess the usefulness of blogs in developing students’ ability to write constructively. We collected data through questionnaires that requested students’ feedback on their attitudes and perspectives pertaining to the integrated blog project and how the project motivated them and helped them increase their interest in writing in English. We found that students had a positive attitude about blogging. The students perceived blogging as an interesting and motivating learning environment because interacting through blogs helped with the critical thinking and peer feedback facets of their writing projects. We also found that social interaction helped students improve their writing skills